Aproximación a la historia de los parques de Bogotá (2006)
This article presents an approach to the historical evolution of Bogota’s parks, based on the analysis of the urban development of the city from the time of its foundation up to the 21st century. It describes the appearance, evolution, and actual condition of the city’s urban parks that nowadays shape Bogota’s Main Ecological Structure, focusing primarily on native and migratory birds that currently frequent them, and on some of the species of trees and bushes thatnow feed them.